Communication of Teachers and Parents of Students in Optimizing Learning During the Pandemic Era at MIN 6 Jembrana Bali - Firman Aulia Ramadhan; Niki Hidayah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2022)
One of the keys to the successful implementation of the learning process during the Covid-19 pandemic is intensive communication between teachers and parents of students. Because without communication there will be obstacles because elementary school students still need guidance from teachers and parents. The purpose of this study was to describe the communication between teachers and parents of students in optimizing learning during the pandemic at MIN 6 Jembrana This research uses a phenomenological qualitative approach. Collecting data in this study using the interview method. To test the validity of the data obtained, researchers used triangulation of data sources and triangulation of methods. The results of this study are: 1) The communication of teachers and parents of students at MIN 6 Jembrana during the Covid-19 pandemic in carrying out the teaching and learning process using the Sambang teacher program, namely visiting student houses to carry out the learning process. In addition, communication between teachers and parents is to form a whatsapp group for each class. 2) Constraints or challenges faced by teachers and parents during the Covid 19 pandemic are limitations in using cellphones, increased spending due to having to buy quotas, and availability of network / internet signal.